Sistem Transitivitas Dalam Teks Pidato Pelantikan Presiden Republik Indonesia Joko Widodo - W Sri Kusuma; I Ketut Darma Laksana (Program Magister Linguistik Universitas Udayana, 2020)
The study aims to determine the transitivity system in the Inaugural Speech of the President of the Republic of Indonesia Joko Widodo. Transitivity studies relate to grammatical elements that can be used to reveal participants involved in an event. This research uses a qualitative approach. The data source of this research was obtained from the President Joko Widodo's Inauguration Speech Text for the 2014-2019 period which was downloaded through the site www.youtube.com. The theory used is the Functional Systemic Linguistic Theory (LSF) proposed by Halliday (1985). The method and data collection technique used is the method of referring to the note taking technique. The method of presenting the results of the analysis of the data used is a general method for applying the presentation of all forms of speech in research in the form of descriptions of words, phrases, groups of phrases, clauses, and texts. The results showed that the types of processes contained in the research data were material, mental, verbal, relational, and behavioral processes. Each process labels its participants. Circumstan which is present in this research data is in the form of time and situation circumferences.